2022
DOI: 10.1136/annrheumdis-2022-eular.2402
|View full text |Cite
|
Sign up to set email alerts
|

Ab1558-Hpr telerheumatology With Primary Care Centers: Feedback From an Experimental Telemedicine Project in Burgundy (2019-2021)

Abstract: BackgroundTelemedicine could be an innovative and sustainable response for rheumatologic advice in areas with low medical density. Improving coordination of investigations, access to allied health members and dedicated telehealth platform may improve the management of many rheumatologic patients.MethodsThis French TeleRheumatology project with multidisciplinary primary care centres was set up in 2019, specifically targeting the Burgundy region in Eastern France and was financed by the Regional Health Agency. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Of the 12 retrospective studies, 7 reported patients being comfortable and satisfied with telemedicine visits 31–33,37–40 . In one study, patients preferred to choose between the option of F2F and telemedicine care 41 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 12 retrospective studies, 7 reported patients being comfortable and satisfied with telemedicine visits 31–33,37–40 . In one study, patients preferred to choose between the option of F2F and telemedicine care 41 .…”
Section: Resultsmentioning
confidence: 99%
“…We identified 14 studies addressing telemedicine satisfaction, including 2 prospective cohort studies and 12 retrospective studies. These were from the US, 30 , 31 , 32 , 33 , 34 , 35 Australia, 36 , 37 the UK, 38 , 39 France, 40 Canada, 41 , 42 and the Netherlands, 43 with sample sizes from 15 to 819 participants, and included patients with RA, CTD, osteoarthritis, PsA, AS, systemic sclerosis, and SLE. All the studies used bespoke satisfaction instruments or surveys, with only one study using a modified version of the validated Telehealth Satisfaction and Usefulness Survey (TeSS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation